Comparable outcomes after busulfan- or treosulfan-based conditioning for allo-HSCT in children with ALL: results of FORUM - Kalwak, Krzysztof; Moser, Laura M; Pötschger, Ulrike; Bader, Peter; Kleinschmidt, Katharina; Meisel, Roland; Dalle, Jean-Hugues; Yesilipek, Akif; Balduzzi, Adriana; Krivan, Gergely; Goussetis, Evgenios; Staciuk, Raquel; et al. (Blood advances, 2025)
The superiority of total body irradiation (TBI)-based vs chemotherapy conditioning for allogeneic hematopoietic stem cell transplantation (allo-HSCT) in children with acute lymphoblastic leukemia (ALL) has been established in the international, prospective phase-3 FORUM study, randomizing 417 patients aged 4-18 years in complete remission (CR), who received allo-HSCT from HLA-matched sibling or unrelated donors. Because of the unavailability of TBI in some regions and to accommodate individual contraindications, this study reports the prespecified comparison of outcomes of patients receiving busulfan (BU)- or treosulfan (TREO)-based regimens from 2013 to 2018. Overall, 180 and 128 patients received BU/thiotepa (THIO)/fludarabine (FLU) or TREO/THIO/FLU, respectively. Data were analyzed as of February 2023, with a median follow-up of 4.2 years (range, 0.3-9.1). 3-year overall survival was 0.71 (BU, 95% confidence interval [0.64-0.77]) and 0.72 (TREO, [0.63-0.79]) and 3-year event-free survival was 0.60 (BU, [0.53-0.67]) and 0.55 (TREO, [0.46-0.63]). The 3-year cumulative incidence of relapse (BU, 0.31 [0.25-0.38]; TREO, 0.36 [0.27-0.44]); and nonrelapse mortality (BU, 0.08 [0.05-0.13]; TREO, 0.09 [0.05-0.15]) were comparable. One case of fatal veno-occlusive disease occurred in each group. No significant differences in acute and chronic graft-versus-host disease (GVHD) or 3-year GVHD-free and relapse-free survival (BU, 0.48 [0.41-0.55]; TREO, 0.45 [0.37-0.54]) were recorded. Outcomes for patients in first and second CR were similar irrespective of the regimen. In conclusion, BU/THIO/FLU or TREO/THIO/FLU regimens can be an alternative to TBI for patients with ALL aged >4 years with contraindications or lack of access to TBI. This trial was registered at www.ClinicalTrials.gov as #NCT01949129.
Keywords: mladiství; výsledek terapie; akutní lymfatická leukemie; mužské pohlaví; nemoc štěpu proti hostiteli; dítě; Transplantation Conditioning; Child; příprava pacienta k transplantaci; Child, Preschool; Hematopoietic Stem Cell Transplantation; ženské pohlaví; transplantace hematopoetických kmenových buněk; Humans; předškolní dítě; Graft vs Host Disease; Transplantation, Homologous; busulfan; Busulfan; homologní transplantace; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Female; Adolescent; Treatment Outcome; lidé; Male